Relationship Between Physical Activity Level and Characteristics of Patients with Cancer: RELAÇÃO ENTRE O NÍVEL DE ATIVIDADE FÍSICA E AS CARACTERÍSTICAS DO PERFIL DE PACIENTES COM CÂNCER - Corrêa, Raphaela Espanha (2021)
Evidences have shown that Physical Activity (PA) can decrease side effects, such as fatigue and pain, as well as promote increase of muscular endurance, oxygen consumption and quality of life) of patients with different phases of cancer treatments. However, studies have demonstrated that patients with cancer diagnosis may show insufficient levels of PA. Therefore, it is necessary to check the profile of such patients. Thus, the aim of this study was to analyze PA level and the sociodemographic and clinical profile of patients with cancer. It is a field study that included 247 patients of both sex, above 18 years old any type of cancer. The International Physical Activity Questionnaire-IPAQ-Bref was used to measure PA and the clinical profile was assessed using a questionnaire. The breast cancer was most common type (32.4%), the mean age was 60.08 ± 13.12 and patients in general have inadequate levels of PA, independent of treatment phase. It was found negative association between age and time of PA (rho=-0.145, p<0.05), years of diagnosis were associated with the level of PA: less than one year of diagnosis can be a significant predictor of low physical activity level (OR= 28.457; 95% CI 1.706 – 474.589; p= 0.020) and for moderate physical activity level (OR= 29.578; 95% CI 1.409 – 620.746; p= 0.029), Implementation of public policies to spread information and to offer PA programs to patients with cancer are needed,  especially in the beginning of  the treatment.